Comparison of emulsifying capacity of two hemicelluloses from moso bamboo in soy oil-in-water emulsions. Issue 8 (28th January 2020) - Li, Yan-Fei; Yue, Pan-Pan; Hao, Xiang; Bian, Jing; Ren, Jun-Li; Peng, Feng; Sun, Run-Cang
Abstract : Oil-in-water food emulsions consisting of natural emulsifiers has been an active field of green scientific inquiry. Abstract : Oil-in-water food emulsions consisting of natural emulsifiers has been an active field of green scientific inquiry. Here, we extract two types of new hemicellulose-based emulsifiers (HH and HL ) from holocellulose and dewaxed materials of bamboo ( Phyllostachys pubescens ), as well as compare their emulsifying soy oil ability, respectively. The main content of HH is arabinoxylan, while the primary composition in HL is glucan. The emulsifying capacity of these two types of hemicellulose-based emulsifiers are evaluated by droplet size distribution, surface charge and optical microscopy. Since HL possesses higher lignin and protein residual contents, the resultant emulsion exhibits smaller droplets and higher emulsion stability. In comparison, HH emulsifier has almost no emulsifying capacity due to the lack of non-polar groups. This study provides insight into the choice of hemicelluloses-based emulsifiers for the formation of stable oil-in-water food emulsions.